Development and validation of a droplet digital PCR assay for sensitive detection and quantification of Phytophthora nicotianae - Liu, Yuanyuan; Li, Jiali; Guo, Zining; Feng, Chao; Gao, Yunhua; Liu, Danmei; Wang, Di (Frontiers in Plant Science, 2025)
Tobacco black shank (TBS) disease, caused by Phytophthora nicotianae (P. nicotianae), poses a significant threat to global agriculture and results in substantial economic losses. Traditional methods, like culture-based techniques and quantitative polymerase chain reaction (qPCR), aid pathogen identification but can be less sensitive for complex samples with low pathogen loads. Here, we developed and validated a droplet digital PCR (ddPCR) assay with high sensitivity and specificity for detecting P. nicotianae. ddPCR and qPCR revealed comparable analytical performance including limit of blank (LoB), limit of detection (LoD), and limit of quantitation (LoQ). For the 68 infectious tobacco root samples and 145 surrounding soil samples, ddPCR demonstrated greater sensitivity, with a higher positive rate of 96.4% vs 83.9%. Receiver operating characteristic (ROC) analysis showed an area under the curve (AUC) of ddPCR was 0.913, compared to 0.885 for qPCR. Moreover, ddPCR provided better quantification accuracy for low pathogen concentrations in soil, suggesting better tolerance to potential PCR inhibitors in soil. These results highlight ddPCR as a robust and reliable tool for early diagnosis in complex samples, offering a valuable tool for improving disease management strategies.